Differential impacts from an extreme cold spell on subtropical vs. tropical specialist bees in southern Florida. Issue 5 (5th May 2016) - Downing, Jason; Borrero, Haydee; Liu, Hong
Abstract: Gradual warming and changes in extreme weather patterns associated with human induced climate change are altering the range distributions of species. However, species responses to climate change are predicted to be more strongly affected by extreme events than by changes in mean values. As a result, measuring species' responses to extreme events in addition to the mean changes in climate are necessary to predict species range limits under future conditions. This study examines the impacts of a cold spell in southern Florida on native and an introduced oil‐collecting bees by examining the bees' interactions with two native plants species. Our results provide evidence of differential impacts from an extreme cold event on a native, subtropical bee vs. an introduced, tropical bee. Specifically, the cold spell had little impact on the abundance of the native bee, while the abundance of the introduced, tropical bee was negatively impacted. Our findings demonstrate that extreme cold spells are important climate change‐related phenomena that can have strong impacts on tropical species distributions and abundances, especially at the threshold of their thermal tolerances. Our approach also provided a rare opportunity to examine these impacts on multiple interacting species, which provides a more realistic assessment of the potential impacts of climate change.